2016
DOI: 10.2174/1568026616666160204121431
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol as a Potential Therapeutic Candidate for the Treatment and Management of Alzheimer';s Disease

Abstract: Resveratrol (3,4',5-trihydroxystilbene) is a naturally occurring phytochemical present in red wine, grapes, berries, chocolate and peanuts. Clinically, resveratrol has exhibited significant antioxidant, anti-inflammatory, anti-viral, and anti-cancer properties. Although resveratrol was first isolated in 1940, it was not until the last decade that it was recognised for its potential therapeutic role in reducing the risk of neurodegeneration, and Alzheimer's disease (AD) in particular. AD is the primary cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 0 publications
0
52
0
2
Order By: Relevance
“…Our study also showed that MRI, aided by targeted superparamagnetic nanoparticles, constituted a noninvasive method for measuring the efficacy of drug treatment using resveratrol, a phytochemical being studied for the treatment of AD to reduce both amyloidosis and neuroinflammation . Several studies have shown that resveratrol provided neuroprotection and facilitated the breakdown of amyloid precursor protein, to promote the removal of Aβ, a neurotoxic component in AD …”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our study also showed that MRI, aided by targeted superparamagnetic nanoparticles, constituted a noninvasive method for measuring the efficacy of drug treatment using resveratrol, a phytochemical being studied for the treatment of AD to reduce both amyloidosis and neuroinflammation . Several studies have shown that resveratrol provided neuroprotection and facilitated the breakdown of amyloid precursor protein, to promote the removal of Aβ, a neurotoxic component in AD …”
Section: Discussionmentioning
confidence: 68%
“…When the 3D data, from the brains of 3X Tg treated with resveratrol, were examined, it was found that (Fig. 8D) as we 8,9 and others [49][50][51][52][53][54] have previously determined, inclusion of 100 ppm resveratrol in the diet of Tg mice resulted in a substantial lowering of the plaque density; in this case by more than 24-fold, however, with a statistically significant (P < 0.0001) increase in the mean Z-score from 31 to 34 (Table 1).…”
Section: Resveratrol Treatment Lowered the Ab Load In The Brainmentioning
confidence: 68%
“…In Nrf2 À/À astrocytes, a decreased mitochondrial antioxidant expression and an inability to up-regulate cellular antioxidants following preconditioned treatment were also recorded. There is much interest in utilizing curcumin and resveratrol for AD therapy due to their influence on amyloid beta, antioxidant and anti-inflammatory properties 113,114 . On the molecular level, as a Michael acceptor, the electrophilic a,b-unsaturated carbonyl groups of curcumin is believed to selectively interact with cysteines on Keap1 enabling the release of Nrf2 for action 115 .…”
Section: Natural Nrf2 Activatorsmentioning
confidence: 99%
“…Resveratrol is a naturally occuring product found abundantly in grapes and red wine with anti-oxidant, antiangiogenic, anti-inflammatory, anti-viral and anti-cancer properties [5]. It is considered an important dietary ingredient associated with the well known "French Paradox" in which drinking wine regularly can reduce the risk of cardiovascular disease, stroke, cancer, and AD [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, resveratrol is a natural polyphenolic stilbenoid (3,5,4′-trihydroxy-trans-stilbene) found in many plant species such as pine trees, grapes, peanuts and berries, as well as in processed food products such as red wine. It is a biologically active compound that acts on different targets in several models of cardiovascular and age related diseases including AD to exert the protective and anti-oxidant effects resulting in reduction of cardiovascular risk factors [5,9,10]. While details of the cardiovascular protective effect is not fully understood, a most likely mechanism is the effect of resveratrol to up-regulate endothelial nitric oxide synthase (eNOS), and scavenge oxygen free radicals which can limit lipid peroxidation and prevent tissue damage [8].…”
Section: Introductionmentioning
confidence: 99%